Political Education amid the Revivalism of Youth Political Volunteers - Marianus M. Tapung (AL-ISHLAH: Jurnal Pendidikan, 2022)
Political education is very important in the life of the state. Practically, the contestation for the regional head election is an opportunity for implementing political education especially for young Manggarai people. As a result, they will have a participatory awareness in building the nation state. This study aims at exploring the basic motivations of young people when joining volunteering communities, analyzing the extent to which socio-political education plays a role in building critical awareness in young people in Manggarai, and offering a form of projection on the sustainability of the transformation of youth participation, from the politics of contestation to the politics of participatory builders. The benefits of this research are providing socio-political education to young people about the importance of involvement in local, regional and national politics, which is based on critical awareness; second, emancipating the critical awareness of the Manggarai community and political stakeholders, in understanding, responding and critically assessing praxis involving youth. This study uses the qualitative method of social criticism of which aims to study the motivations of young Manggarai people when joining the political volunteer community, the nature and goals of the volunteer community and the way volunteers work. Data were obtained through personal/group interviews, photo documentation on social media (facebook, youtube) and online mass media, as well as several field activities involving the author. The data were analyzed qualitatively with a triangulation pattern on phenomena, interviews, and documentation processed from social media and online media reports.